2014 24th International Conference on Field Programmable Logic and Applications (FPL) 2014
DOI: 10.1109/fpl.2014.6927406
|View full text |Cite
|
Sign up to set email alerts
|

An FPGA-optimized architecture of horn and schunck optical flow algorithm for real-time applications

Abstract: Optical flow estimation of image sequences is one of the key elements for motion detection. However, processing the optical flow in real-time is still an open task due to its computationally expensive nature. In this paper we present an FPGA-optimized architecture for optical flow estimation based on the algorithm of Horn and Schunck. While existing FPGArealizations are only partly real-time capable, on a Stratix IV our architecture enables the computation of the optical flow for each pixel of a frame with 640… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…CMLA's IPol website [4] also provides various codes of recent algorithms. Optimized implementations of optical flow algorithms were the subject of numerous works on FPGA [5], [6], [7], [8] and on GPU [9], [10], [11], [12], but few on CPU [11], [13]. It should also be noted that optical flow estimations based on machine learning are gaining in popularity in the scientific community [14], [15].…”
Section: Optical Flow Iterative Algorithmsmentioning
confidence: 99%
“…CMLA's IPol website [4] also provides various codes of recent algorithms. Optimized implementations of optical flow algorithms were the subject of numerous works on FPGA [5], [6], [7], [8] and on GPU [9], [10], [11], [12], but few on CPU [11], [13]. It should also be noted that optical flow estimations based on machine learning are gaining in popularity in the scientific community [14], [15].…”
Section: Optical Flow Iterative Algorithmsmentioning
confidence: 99%
“…Approach vs. characteritics non-tiled on-chip [6] non-tiled off-chip [5], [9] partial oblique tiling [10] full oblique tiling (ours) overlapped tiling [7] Domain size scalability…”
Section: B Overview Of the Execution Datapathmentioning
confidence: 99%
“…The non-tiled variants [5], [6], [9] (recall Table I) may be viewed as designs with tile size in the time dimension set to 1, and the remaining dimensions equal to the problem size. These designs do not exploit temporal locality, and are not suited for iterative stencils.…”
Section: Comparison With Earlier Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study [20] showed that pipelined image processing systems can achieve linear acceleration. Outstanding computing performances of parallel-pipelined modules for the Horn-Schunck optical flow algorithm were demonstrated in papers [31,35].…”
Section: Pipeline Data Processingmentioning
confidence: 99%